Rola idoli w kształtowaniu tożsamości młodzieży – na przykładzie Justina Biebera - Zarzycka, Maja (Studia Edukacyjne, 2022)
The article is devoted to the role of idols in shaping the identity of young people. In the first part, the author introduced the family and school as the main educational authorities of children. This part shows the role of the church and the peer group. During the maturation stage, mass media also appear, and with them idols who assume the role of authorities. A description of who can be called an idol has been given, and several subdivisions have been made to represent the existing celebrity types. The model of adolescents’ addiction to them and the negative consequences that often follow were also described. In the second part of the article, using the example of the famous singer Justin Bieber, the author presented the way in which idols affect young people. First, the life of this star was described and the events which affected his popularity. Several of his songs have also been interpreted. At the very end, comments on Justin Bieber from an online forum were presented, illustrating how the fans and the rest of the public perceive the singer. The last part briefly shows what pedagogical contexts can be introduced to the identity and activity of an idol such as Justin Bieber.